2018
DOI: 10.1080/19490976.2018.1549420
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo characterization of Clostridium scindens bile acid transformations

Abstract: The human gut hosts trillions of microorganisms that exert a profound influence on human biology. Gut bacteria communicate with their host by secreting small molecules that can signal to distant organs in the body. Bile acids are one class of these signaling molecules, synthesized by the host and chemically transformed by the gut microbiota. Among bile acid metabolizers, bile acid 7-dehydroxylating bacteria are commensals of particular importance as they carry out the 7-dehydroxylation of liver-derived primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 66 publications
9
77
0
1
Order By: Relevance
“…Conversion of CDCA to a-and bmuricholic acid (MCA) was observed ( Figure S4), however little conversion of MCA to murideoxycholic acid (MDCA) and w-MCA was detected. This con rmed the mice in this study housed a microbial consortium of human bacteria, as only limited MDCA has been shown to be generated by the host [32], and human mixed fecal bacteria and bile acid 7a-dehydroxylating clostridia appear to be unable to metabolize MCA to MDCA and w-MCA [12,30,31].…”
Section: Resultssupporting
confidence: 64%
“…Conversion of CDCA to a-and bmuricholic acid (MCA) was observed ( Figure S4), however little conversion of MCA to murideoxycholic acid (MDCA) and w-MCA was detected. This con rmed the mice in this study housed a microbial consortium of human bacteria, as only limited MDCA has been shown to be generated by the host [32], and human mixed fecal bacteria and bile acid 7a-dehydroxylating clostridia appear to be unable to metabolize MCA to MDCA and w-MCA [12,30,31].…”
Section: Resultssupporting
confidence: 64%
“…Conversion of CDCA to α-and βmuricholic acid (MCA) was observed ( Figure S4); however, little conversion of MCA to murideoxycholic acid (MDCA) and ω-MCA was detected. This con rmed the mice in this study housed a microbial consortium of human bacteria, as human mixed fecal bacteria and bile acid 7α-dehydroxylating clostridia appear to be unable to metabolize MCA to MDCA and ω-MCA [11,[13][14][15]. Additionally, MDCA has been shown to be generated by the host [16].…”
Section: Resultssupporting
confidence: 61%
“…This analysis also indicated enrichment of genes associated with CCAAT/enhancer-binding proteins, known to be important for GMP and neutrophil differentiation and expansion (refs. 30 , 31 and Supplemental Figure 3F ). Quantitative PCR of sorted marrow GMPs confirmed that significant changes in expression occurred in JMJD3 ( Supplemental Figure 3, C–E, G, J, and K ) and 2 CCAAT/enhancer-binding protein genes important in granulopoiesis ( 28 , 29 ), C/EBPA ( Supplemental Figure 3H ) and C/EBPB ( Supplemental Figure 3I ).…”
Section: Resultsmentioning
confidence: 96%